Phytosociology of the vegetation communities of the Stelvio Pass area. Issue 2 (1st December 2021) - Malfasi, Francesco; Cannone, Nicoletta
ABSTRACT: High elevation areas are sensitive and vulnerable to climate change and exhibited relatively rapid changes in response to warming involving changes of floristic composition, species upward migration, shrub and tree encroachment and surface area changes. For this reason, it is important to provide quantitative studies as tools allowing a long-term monitoring of vegetation in response to climate change. The Stelvio Pass area is a high elevation site located in the European Alps, and a unique case study on the alpine range providing historical detailed information on vegetation with the availability of phytosociological maps of vegetation elaborated in 1953 and 2003. Here we show and describe an updated and detailed phytosociological vegetation mapping which will constitute a robust base for the monitoring and quantitative assessment of any impacts of future climate and/or environmental change as well as a tool to plan suitable vegetation and biodiversity conservation actions in the alpine environment.